Adaptive evolution of the heat-shock response in the Antarctic psychrophilic ciliate, Euplotes focardii: hints from a comparative determination of the hsp70 gene structure - La Terza, Antonietta; Passini, Valerio; Barchetta, Sabrina; Luporini, Pierangelo (Antarctic Science, 2007)
The Antarctic psychrophilic ciliate Euplotes focardii manifests a dramatic reduction in the activation of its hsp70 gene in response to a heat-shock, while oxidative and chemical stresses activate the transcription of this gene to appreciable extents. To investigate the genetic causes of this eccentric behaviour of E. focardii in the hsp70 gene transcription activation, we carried out a comparative structural analysis of this gene between E. focardii and another Antarctic Euplotes, E. nobilii, which manifests a psychrotrophic behaviour and an inducible thermal response. No substantial difference was detected in the organization of the hsp70 5’ promoter region, both species bearing canonical regulatory cis-acting elements deputed to bind transcriptional trans-activating factors. Adenine-rich elements favouring mRNA degradation were instead detected in the hsp70 3’ regulatory region of E. nobilii, but not in that of E. focardii. These observations lend further support to the hypothesis that the causes of the Euplotes focardii unresponsiveness to thermal stress resides in some structural, or functional modifications of transcriptional trans-activating factors.